Method for producing adhesive sheet, and adhesive sheet
By irradiating ultraviolet rays on the photocured adhesive sheet and coating the ultraviolet absorber solution, the deterioration of curing properties and physical properties caused by the ultraviolet absorber are solved, and the stability of the adhesive layer and efficient ultraviolet shielding are achieved, thereby improving the stability of the adhesive layer. The design and use efficiency of adhesive sheets.
Patent Information
- Application Number
- CN202411420584.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2021-03-23
- Filing Date
- 2021-03-24
- Publication Date
- 2024-12-13
AI Technical Summary
When the existing photocuring adhesive sheet is mixed with ultraviolet absorbers, it is easy to cause deterioration of curing properties, lower productivity, differences in physical properties on the front and back, and changes in peeling force of the peeling sheet, which affects the design and use efficiency of the adhesive sheet. .
By irradiating ultraviolet rays on the adhesive layer to cure it, and then applying the ultraviolet absorber solution to penetrate along the thickness direction, controlling the absorber concentration gradient, thereby maintaining the transparency and excellent physical properties of the adhesive layer, and avoiding the problem of the leakage of the adhesive layer. Curing problems caused by ultraviolet absorbers.
The curing properties, peeling force consistency and ultraviolet shielding of the adhesive layer are effectively controlled, design changes are reduced, production efficiency and the use effect of the adhesive sheet.
Smart Images

Figure CN119119903A_ABST
Abstract
Description
[0001] This application is a divisional application of an application with a filing date of March 24, 2021, an application number of 202180024678.1, and an invention name of “Method for manufacturing adhesive sheet and adhesive sheet”. Technical Field
[0002] The present invention relates to a method for producing an adhesive sheet having a transparent adhesive layer and an adhesive sheet obtainable by the production method. In particular, the present invention relates to a method for producing an adhesive sheet having a transparent adhesive layer that can be used to bond a transparent optical component to another optical component and an adhesive sheet obtainable by the production method. Background Art
[0003] Image display devices such as liquid crystal display devices and organic EL display devices are composed of optical component stacks stacked with transparent cover components such as polarizing films, phase difference films, cover glasses, and other various transparent optical components. In order to join these optical components, an adhesive sheet containing a transparent adhesive layer is used. That is, an adhesive sheet is arranged between two optical components to be joined, and the two optical components are joined by pressing them against each other to form an optical component stack. In addition, in the manufacturing process of optical products, an adhesive sheet having an adhesive layer on one side of a substrate film is usually used as a surface protection film for preventing the aforementioned optical components from being damaged or dirt from adhering.
[0004] In addition, in an image display device with a touch panel, a transparent and conductive printed layer such as patterned ITO (indium tin oxide) is formed on the surface of the optical component. Furthermore, silver and copper pulling wiring is formed on the peripheral portion. In addition, a black shielding portion is usually printed in a frame shape on the edge of the transparent cover member. For the adhesive sheet that joins such an optical component with a printed layer and wiring, it is required to have a height difference absorption property such that no bubbles remain in the printed height difference.
[0005] As such an adhesive sheet, a solvent-free photocurable adhesive sheet is widely used (see, for example, Patent Document 1). The photocurable adhesive sheet is partially uncured (semi-cured) before curing and has high fluidity, so it has the following advantages: high absorption of height difference, and subsequent photocuring based on ultraviolet irradiation can improve bonding reliability.
[0006] On the other hand, in image display devices, in order to suppress the degradation of components in the image display device caused by incident ultraviolet rays, ultraviolet shielding properties are sometimes sought. In particular, organic compounds are used as light-emitting elements in organic EL display devices, so the degradation caused by ultraviolet rays is faster than that of liquid crystal display devices. In addition, optical components such as polarizing films and protective films are gradually thinned, and the light resistance to ultraviolet rays is reduced, so an ultraviolet absorbing layer must be provided. For example, it is known to use an adhesive sheet having an ultraviolet absorbing layer containing an ultraviolet absorber (for example, see Patent Document 2).
[0007] On the other hand, a double-sided adhesive sheet of a type that does not have a substrate (sometimes referred to as a "substrate-free adhesive sheet" in this specification) is used in a form protected by release sheets on both sides. The bonding of optical components using a substrate-free adhesive sheet is carried out according to the following steps: First, the single-sided release sheet is peeled off from the adhesive sheet and attached to the first component, and the remaining other release sheet is peeled off and attached to the second component. At this time, when the force (peeling force) required to peel off the two release sheets is similar, the so-called "back-to-back" problem will arise, that is, during the stage of peeling off the first release sheet, the (second) release sheet on the opposite side is also peeled off. Therefore, the adhesive sheet without a substrate is designed in such a way that the peeling forces of the two release sheets are different from each other.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Publication No. 2016-222914
[0011] Patent Document 2: Japanese Patent Application Publication No. 2012-211305 Summary of the invention
[0012] Problem that the invention aims to solve
[0013] The adhesive sheet of the aforementioned patent document 2 is composed of an ultraviolet absorbing layer obtained by mixing an ultraviolet absorber in an adhesive composition and uniformly dissolving it. However, since a sufficient amount of ultraviolet absorber is mixed to impart ultraviolet shielding properties to the adhesive composition, there is a problem of affecting the physical properties and curability of the adhesive. In particular, when a photocurable adhesive sheet mixed with an ultraviolet absorber is cured by irradiating ultraviolet rays, there is a problem that the ultraviolet rays are absorbed by the ultraviolet absorber, the curability deteriorates, and the productivity decreases.
[0014] In addition, the photocurable adhesive sheet in which the ultraviolet absorber is uniformly dissolved has the problem of differences in physical properties such as adhesion and viscoelasticity between the front and back sides of the adhesive sheet. This is because the ultraviolet rays are absorbed by the ultraviolet absorber during the process of passing through the inside of the adhesive layer, and the deeper from the ultraviolet irradiation side surface, the lower the ultraviolet irradiance, resulting in a difference in curing speed between the front and back sides.
[0015] Furthermore, in the adhesive sheet without a substrate in which the ultraviolet absorber is uniformly dissolved in the adhesive layer, there is also a problem that the design of the difference in the peeling force of the two release sheets changes. That is, as a countermeasure to the deterioration of curability caused by the ultraviolet absorber, if the amount of polymerization initiator and the amount of ultraviolet irradiation light are increased, the peeling force of the release sheet on the irradiated side will also become larger than the design, and as a result, the following problems may occur: it is difficult to peel using a peeling machine; the peeling forces of the two release sheets are similar and move in opposite directions; the peeling forces of the two release sheets are reversed, etc. In addition, when the peeling force becomes larger, when the remaining release sheet is peeled off after being attached to the first component, the adhesive sheet is stretched and deformed by the force applied to it, so it may also be a problem that the adhesive sheet cannot be perfectly attached.
[0016] Therefore, when a UV absorber is added to a photocurable adhesive sheet, in order to maintain curability while reducing physical property changes such as differences in physical properties between the front and back sides and changes in the peeling force of the release sheet, it is necessary to design the adhesive composition such as the amount of UV absorber added, the thickness of the adhesive sheet, and the curing conditions such as UV irradiance from scratch.
[0017] In particular, in recent years, as image display devices have become thinner, there has been an increasing demand for thinner pressure-sensitive adhesive layers and higher concentrations of ultraviolet absorbers contained in pressure-sensitive adhesive compositions, and the above-mentioned problem has become more prominent.
[0018] The present invention has been conceived based on the above situation, and its purpose is to provide a method for manufacturing an adhesive sheet, which can be easily designed without causing changes in physical properties such as a decrease in productivity due to deterioration of curing properties, differences in physical properties between the front and back sides, and changes in the peeling force of a peeling sheet, even when a UV absorber is mixed into a photocurable adhesive sheet.
[0019] Another object of the present invention is to provide an adhesive sheet that can be easily designed without causing a decrease in productivity due to deterioration in curability, a difference in physical properties between the front and back surfaces, or a change in the peeling force of a release sheet, even when a UV absorber is compounded into the photocurable adhesive sheet.
[0020] Solutions for solving problems
[0021] The inventors of the present invention have conducted intensive research to achieve the above-mentioned purpose, and as a result, have found that by supplying a UV absorber to the adhesive layer after curing the adhesive layer by irradiating the adhesive layer with UV rays, it is possible to obtain an adhesive sheet that minimizes the influence on the curability of the adhesive layer, the difference in physical properties between the front and back surfaces, and the change in the peeling force of the release sheet, and that has excellent physical properties of the adhesive layer, does not cause the above-mentioned problems associated with the change in the peeling force of the release sheet, and has excellent UV shielding properties. The present invention has been completed based on these findings.
[0022] That is, the first aspect of the present invention provides a method for producing an adhesive sheet, comprising the following steps:
[0023] forming an adhesive layer composed of a transparent photocurable adhesive matrix material on a support,
[0024] irradiating the adhesive layer with ultraviolet rays to cure the adhesive layer,
[0025] Prepare a solution of UV absorber,
[0026] The solution is applied to one surface of the cured adhesive layer, so that the ultraviolet absorber contained in the solution penetrates from the one surface of the adhesive layer in the thickness direction.
[0027] The adhesive layer is dried.
[0028] By irradiating the adhesive layer with ultraviolet rays before adding the ultraviolet absorber to the adhesive layer, the adhesive layer can be cured without being affected by the ultraviolet absorber. Therefore, the physical property changes of the adhesive layer or the release sheet such as the decrease in productivity caused by the deterioration of curability due to the ultraviolet absorber and the difference in physical properties between the front and back surfaces can be controlled to a minimum.
[0029] By applying a solution of a UV absorber to the adhesive layer after curing, the UV absorber is infiltrated into the adhesive layer. Thus, sufficient UV shielding properties can be imparted to the adhesive layer. In addition, by infiltrating the UV absorber in the state of a solution, the transparency of the adhesive layer is maintained.
[0030] Thereafter, the adhesive layer is dried by heating, etc. Through this process, the adhesive layer is restored to a state close to that before coating. That is, since the adhesive layer is temporarily cured, the physical properties such as adhesion and viscoelasticity are restored to a state close to that before coating the aforementioned solution.
[0031] Since the adhesive layer is cured before the ultraviolet absorber is applied, once the composition, curing conditions, physical properties, peeling force of the release sheet, etc. of the adhesive composition are determined, there is no need to redesign the composition and peeling force of the release sheet achieved by mixing the ultraviolet absorber, and the thickness of the adhesive layer can be easily changed. In addition, by changing the coating conditions of the ultraviolet absorber solution thereafter, the ultraviolet absorption function applied to the adhesive layer can be controlled. In this way, since the physical property control of the adhesive layer and the release sheet can be separated from the control of the ultraviolet absorption function, there is no need to design the adhesive layer from scratch for changes in the thickness of the adhesive layer, the ultraviolet absorption function, and the peeling force of the release sheet, and the efficiency is good.
[0032] In the method for producing the adhesive sheet according to the first aspect of the present invention, the solution of the ultraviolet absorber may be a solution obtained by dissolving the ultraviolet absorber in a solvent, and the method may include the step of drying the adhesive layer to evaporate the solvent of the solution.
[0033] By applying a solution obtained by dissolving a UV absorber in a solvent to the cured adhesive layer, the solvent penetrates into the adhesive layer, causing the adhesive layer to swell, and the UV absorber dissolved in the solvent penetrates into the adhesive layer swollen by the solvent. Thus, sufficient UV shielding properties can be imparted to the adhesive layer, and the transparency of the adhesive layer can be maintained by allowing the UV absorber to penetrate in the form of a solution.
[0034] The solvent that has penetrated into the adhesive layer evaporates by heating, etc., and the adhesive layer returns to a state close to that before swelling. That is, since the adhesive layer is temporarily cured, the physical properties such as adhesion and viscoelasticity return to a state close to that before the solution is applied.
[0035] In the method for manufacturing an adhesive sheet of the first aspect of the present invention, the solution of the ultraviolet absorber may further contain a pigment compound whose maximum absorption wavelength of the absorption spectrum exists in the wavelength region of 380 to 430 nm. In addition, the method for manufacturing an adhesive sheet of the first aspect of the present invention may further include the following steps: preparing a solution of a pigment compound whose maximum absorption wavelength of the absorption spectrum exists in the wavelength region of 380 to 430 nm, and applying the solution on one surface of the cured adhesive layer. These structures are preferred from the viewpoint of being able to impart to the adhesive layer the function of absorbing light in the wavelength region (380 nm to 430 nm) on the longer wavelength side than the ultraviolet absorber, and more effectively suppressing the degradation of organic EL elements, etc.
[0036] The solution of the pigment compound may be a solution obtained by dissolving the pigment compound in a solvent.
[0037] The method for producing the adhesive sheet of the first aspect of the present invention may further include the step of laminating a release sheet to the surface of the adhesive layer opposite to the support. Laminating a release sheet is preferred from the viewpoint of protecting the surface of the adhesive layer.
[0038] In the method for producing the adhesive sheet of the first aspect of the present invention, the maximum absorption wavelength of the absorption spectrum of the ultraviolet absorber preferably exists in the wavelength region of 300 to 400 nm. This configuration can effectively suppress the degradation of image display devices, especially organic EL display devices, caused by UVA.
[0039] In addition, a second aspect of the present invention provides an adhesive sheet, characterized in that:
[0040] The invention comprises a support and a transparent adhesive layer on the support,
[0041] The adhesive layer is formed of a transparent photocurable adhesive matrix material and is a single layer having two opposing main surfaces.
[0042] The adhesive layer contains a UV absorber dissolved therein.
[0043] When the above-mentioned single-layer adhesive layer is divided into two equal parts along the thickness direction,
[0044] The concentration of the ultraviolet absorber in a region to which the first main surface, which is one of the two main surfaces, belongs is different from the concentration of the ultraviolet absorber in a region to which the other main surface, which is the second main surface, belongs.
[0045] The adhesive sheet of the second aspect of the present invention can be obtained by the manufacturing method of the adhesive sheet of the first aspect of the present invention. By applying a solution of a UV absorber on one side of the adhesive layer and making it penetrate, the concentration difference of the UV absorber can be generated on the front and back sides of the adhesive layer. As mentioned above, the adhesive sheet that can be generated by the formation can control the physical property changes such as the reduction in productivity caused by the deterioration of the curability caused by the UV absorber, the physical property difference on the front and back sides, and the peeling force change of the peeling sheet to the minimum limit.
[0046] It should be noted that in the method for manufacturing the adhesive sheet of the first aspect of the present invention, the concentration of the ultraviolet absorber on the front and back sides of the adhesive layer may be the same or substantially the same, depending on the thickness of the adhesive layer, the penetration time of the ultraviolet absorber, etc. Therefore, the situation in which the concentration of the ultraviolet absorber on the front and back sides of the adhesive layer is the same or substantially the same as that of the adhesive sheet can be obtained by the method for manufacturing the adhesive sheet of the first aspect of the present invention is also included in the present invention.
[0047] The adhesive sheet of the second aspect of the present invention may further dissolve a pigment compound whose maximum absorption wavelength of the absorption spectrum exists in the wavelength region of 380 to 430 nm. This configuration is preferred from the viewpoint of being able to impart to the adhesive layer the function of absorbing light in the wavelength region (380 to 430 nm) on the long wavelength side compared to the ultraviolet absorber and more effectively suppressing the deterioration of organic EL elements, etc.
[0048] The adhesive sheet of the second aspect of the present invention is preferably: the difference between the adhesive force (N / 10mm) of the first main surface and the adhesive force (N / 10mm) of the second main surface is 1.0N / 10mm or less. It is preferred from the viewpoint that two transparent optical components can be joined without a difference in adhesive force through this structure. The difference in adhesive force (N / 10mm) is preferably 0.5N / 10mm or less, and more preferably 0.3N / 10mm or less.
[0049] In the adhesive sheet of the second aspect of the present invention, the adhesive layer is preferably an adhesive layer that is cured by ultraviolet irradiation. This configuration is preferred from the viewpoint of being able to minimize changes in physical properties such as reduction in productivity caused by deterioration of curability due to the ultraviolet absorber, differences in physical properties between the front and back surfaces, and changes in the peeling force of the peeling sheet.
[0050] In the adhesive sheet of the second aspect of the present invention, it is preferred that: the second main surface faces the support, and the concentration of the ultraviolet absorber in the area to which the first main surface belongs is higher than the concentration of the ultraviolet absorber in the area to which the second main surface belongs. This configuration can be obtained by applying a solution of the ultraviolet absorber to the first main surface.
[0051] In the second aspect of the adhesive sheet of the present invention, it is preferred that the single photocurable adhesive layer has a concentration gradient of the ultraviolet absorber along the thickness direction. This configuration can be obtained by applying a solution of the ultraviolet absorber to one main surface of the adhesive layer.
[0052] In the adhesive sheet of the second aspect of the present invention, it is preferred that the support body is formed by a release sheet. In this case, the support body formed by the release sheet is preferably arranged on both sides of the adhesive layer. It is preferred from the viewpoint that the support body can be bonded to the transparent optical member after peeling by making the release sheet.
[0053] In the adhesive sheet of the second aspect of the present invention, it is preferred that the maximum absorption wavelength of the absorption spectrum of the ultraviolet absorber exists in the wavelength region of 300 to 400 nm. This configuration can effectively suppress the degradation of image display devices, especially organic EL display devices, caused by UVA.
[0054] In the adhesive sheet of the second aspect of the present invention, the thickness of the adhesive layer is preferably 5 μm to 500 μm. If the thickness of the adhesive layer is within this range, it is suitable for forming a concentration gradient of the ultraviolet absorber along the thickness direction of the adhesive layer. The thickness of the adhesive layer is more preferably 5 μm to 400 μm, and further preferably 50 μm to 400 μm.
[0055] Effects of the Invention
[0056] According to the method for manufacturing an adhesive sheet and the adhesive sheet of the present invention, even when a UV absorber is compounded into a photocurable adhesive sheet, physical property changes such as a decrease in productivity due to deterioration in curability of the adhesive layer, a difference in physical properties between the front and back surfaces, and a change in the peeling force of the release sheet are unlikely to occur.
[0057] Furthermore, it is not necessary to design the pressure-sensitive adhesive layer from scratch to change the thickness of the pressure-sensitive adhesive layer, the ultraviolet absorption function, or the release of the release sheet, and this is highly efficient. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 The present invention shows processes for implementing an embodiment of a method for manufacturing an adhesive sheet of the present invention, wherein (a) is a schematic diagram showing an adhesive layer forming process, (b) is a schematic diagram showing an adhesive layer curing process, (c) is a schematic diagram showing a solution coating process, (d) is a schematic diagram showing a solution penetration process, and (e) is a schematic diagram showing a drying process.
[0059] Figure 2 (a) is a cross-sectional view showing one embodiment of the adhesive sheet of the present invention, Figure 2 (b) is a cross-sectional view showing another embodiment of the adhesive sheet of the present invention.
[0060] Figure 3 This is a cross-sectional view of an optical member laminated body showing an example of the simplest embodiment using the adhesive sheet of the present invention.
[0061] Figure 4 This is a cross-sectional view showing an embodiment in which a pressure-sensitive adhesive layer is applied to a structure in which a patterned transparent conductive layer is formed.
[0062] Figure 5 It is a graph showing the TOF-SIMS analysis results of the adhesive sheets of Example 10 and Comparative Example 9. Figure 5 (a) is the result of Example 10, Figure 5 (b) is the result of Comparative Example 9. Figure 5In the graph, the scale of the left vertical axis represents the intensity of butyl acrylate (BA) and N-vinyl pyrrolidone (NVP), and the scale of the right vertical axis represents the intensity of the ultraviolet absorber (Tinosorb S). DETAILED DESCRIPTION
[0063] Hereinafter, embodiments of the present invention will be described with reference to the drawings, but the present invention is not limited thereto and is merely an example.
[0064] Figure 1 (a) to (e) are views schematically showing steps of one embodiment of a method for producing a pressure-sensitive adhesive sheet according to the first aspect of the present invention.
[0065] First, if Figure 1 As shown in (a) of FIG. 1 , an adhesive layer 10 made of a transparent photocurable adhesive matrix material is formed on a support S1 (adhesive layer forming step).
[0066] The support is not particularly limited, but preferably a plastic film. As the raw materials of the plastic film, polyester resins such as polyethylene terephthalate (PET), acrylic resins such as polymethyl methacrylate (PMMA), polycarbonate, cellulose triacetate (TAC), polysulfone, polyarylate, polyimide, polyvinyl chloride, polyvinyl acetate, polyethylene, polypropylene, ethylene-propylene copolymer, cyclic olefin polymers such as "ARTON" (cyclic olefin polymer, manufactured by JSR Corporation), and "ZEONOR" (cyclic olefin polymer, manufactured by ZEON Corporation, Japan) can be cited. It should be noted that only one of these plastic materials can be used, or two or more can be used.
[0067] The support may be a release sheet. The release sheet is not particularly limited, and examples thereof include plastic films surface-treated with a release agent such as a silicone-based, long-chain alkyl-based, fluorine-based, or molybdenum sulfide release agent.
[0068] As long as the aforementioned photocurable adhesive matrix material is a transparent material with adhesiveness that can be used in optical applications, there is no particular limitation. It can be appropriately selected from, for example, acrylic adhesives, rubber adhesives, silicone adhesives, polyester adhesives, urethane adhesives, epoxy adhesives and polyether adhesives for use. From the viewpoints of transparency, processability and durability, it is preferred to use acrylic adhesives. The aforementioned photocurable adhesive matrix material can use any of the aforementioned adhesives alone, or it can also use two or more in combination. The acrylic polymer used as the matrix polymer of the acrylic adhesive has no particular meaning, and is preferably a homopolymer or copolymer of a monomer with (meth) alkyl acrylate as the main component. Here, the expression "(meth) acrylic acid" is used to refer to either or both of "acrylic acid" and "methacrylic acid", and other situations are the same. In the present invention, the term acrylic polymer is used in the sense of including other monomers that can copolymerize with it in addition to the above-mentioned (meth) alkyl acrylate.
[0069] When the aforementioned photocurable adhesive matrix material contains an acrylic polymer as an acrylic adhesive, the acrylic polymer preferably contains monomer units derived from an alkyl acrylate having a linear or branched alkyl group and / or an alkyl methacrylate having a linear or branched alkyl group as main monomer units with the largest weight proportion.
[0070] Examples of the (meth)acrylic acid alkyl ester having a linear or branched alkyl group used in the monomer unit forming the acrylic polymer, that is, the (meth)acrylic acid alkyl ester having a linear or branched alkyl group contained in the monomer component forming the acrylic polymer, include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, sec-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, amyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, and tert-butyl (meth)acrylate. Alkyl (meth)acrylates having a linear or branched alkyl group with 1 to 20 carbon atoms, such as 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate. As the alkyl (meth)acrylate used for the acrylic polymer, one alkyl (meth)acrylate may be used, or two or more alkyl (meth)acrylates may be used. In the present embodiment, as the alkyl (meth)acrylate used for the acrylic polymer, at least one selected from the group consisting of n-butyl acrylate, 2-ethylhexyl acrylate, and isostearyl acrylate is preferably used.
[0071] The ratio of the monomer units derived from the (meth)acrylic acid alkyl ester having a linear or branched alkyl group in the acrylic polymer is preferably 50% by weight or more, more preferably 60% by weight or more, more preferably 70% by weight or more, more preferably 80% by weight or more, and more preferably 90% by weight or more. In other words, the ratio of the (meth)acrylic acid alkyl ester in the monomer component composition of the raw material for forming the acrylic polymer is preferably 50% by weight or more, more preferably 60% by weight or more, more preferably 70% by weight or more, more preferably 80% by weight or more, and more preferably 90% by weight or more.
[0072] The acrylic polymer contained in the aforementioned photocurable adhesive matrix material may include monomer units derived from alicyclic monomers. As alicyclic monomers used to form monomer units of acrylic polymers, that is, alicyclic monomers contained in monomer components used to form the acrylic polymers, for example, cycloalkyl (meth)acrylates, (meth)acrylates having a bicyclic hydrocarbon ring, and (meth)acrylates having a hydrocarbon ring of three or more rings can be listed. As cycloalkyl (meth)acrylates, for example, cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, cycloheptyl (meth)acrylate, and cyclooctyl (meth)acrylate can be listed. As (meth)acrylates having a bicyclic hydrocarbon ring, for example, bornyl (meth)acrylate and isobornyl (meth)acrylate can be listed. As (meth)acrylates having three or more hydrocarbon rings, for example, dicyclopentanyl (meth)acrylate, dicyclopentyloxyethyl (meth)acrylate, tricyclopentanyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, and 2-ethyl-2-adamantyl (meth)acrylate can be cited. As alicyclic monomers for acrylic polymers, one alicyclic monomer can be used, or two or more alicyclic monomers can be used. In the present embodiment, as alicyclic monomers for acrylic polymers, at least one selected from the group consisting of cyclohexyl acrylate, cyclohexyl methacrylate, isobornyl acrylate, and isobornyl methacrylate is preferably used.
[0073] From the viewpoint of achieving appropriate flexibility of the photocurable adhesive matrix material formed by including the acrylic polymer, the proportion of the monomer units derived from the alicyclic monomer in the acrylic polymer is preferably 5 to 60 wt %, more preferably 10 to 50 wt %, and even more preferably 12 to 40 wt %.
[0074] The acrylic polymer contained in the aforementioned photocurable adhesive matrix material may contain a monomer unit derived from a hydroxyl-containing monomer. A hydroxyl-containing monomer is a monomer having at least one hydroxyl group in the monomer unit. When the acrylic polymer in the photocurable adhesive matrix material contains a hydroxyl-containing monomer unit, it is easy to make the photocurable adhesive matrix material have adhesiveness and appropriate cohesion.
[0075] As the hydroxyl-containing monomer used to form the monomer unit of the acrylic polymer, that is, the hydroxyl-containing monomer contained in the monomer component used to form the acrylic polymer, for example, hydroxyl-containing (meth)acrylates, vinyl alcohol and allyl alcohol can be listed. As the hydroxyl-containing (meth)acrylates, for example, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, hydroxyoctyl (meth)acrylate, hydroxydecyl (meth)acrylate, hydroxylauryl (meth)acrylate and (4-hydroxymethylcyclohexyl)methyl (meth)acrylate can be listed. As the hydroxyl-containing monomer used for the acrylic polymer, one hydroxyl-containing monomer can be used, or two or more hydroxyl-containing monomers can be used. In this embodiment, as the hydroxyl-containing monomer used for the acrylic polymer, at least one selected from the group consisting of 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, 4-hydroxybutyl acrylate and 4-hydroxybutyl methacrylate is preferably used.
[0076] The proportion of monomer units derived from hydroxyl-containing monomers in the acrylic polymer is preferably 1% by weight or more, more preferably 2% by weight or more, more preferably 3% by weight or more, more preferably 7% by weight or more, more preferably 10% by weight or more, and more preferably 15% by weight or more. The proportion of monomer units derived from hydroxyl-containing monomers in the acrylic polymer is preferably 35% by weight or less, more preferably 30% by weight or less. These configurations related to the proportion of hydroxyl-containing monomers are suitable for achieving adhesion and appropriate cohesive force in a photocurable adhesive matrix material formed by including the acrylic polymer.
[0077] The acrylic polymer contained in the aforementioned photocurable adhesive matrix material may contain a monomer unit derived from a nitrogen-containing monomer. A nitrogen-containing monomer is a monomer having at least one nitrogen atom in the monomer unit. When the acrylic polymer in the photocurable adhesive matrix material contains a nitrogen-containing monomer unit, it is easy to make the photocurable adhesive matrix material hard and have good bonding reliability.
[0078] Examples of nitrogen-containing monomers for forming the monomer units of the acrylic polymer, i.e., nitrogen-containing monomers contained in the monomer components for forming the acrylic polymer, include N-vinyl cyclic amides and (meth)acrylamides. Examples of N-vinyl cyclic amides that are nitrogen-containing monomers include N-vinyl-2-pyrrolidone, N-vinyl-2-piperidone, N-vinyl-3-morpholinone, N-vinyl-2-caprolactam, N-vinyl-1,3-oxazin-2-one, and N-vinyl-3,5-morpholinedione. Examples of (meth)acrylamides that are nitrogen-containing monomers include (meth)acrylamide, N-ethyl (meth)acrylamide, N-isopropyl (meth)acrylamide, N-n-butyl (meth)acrylamide, N-octyl (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N,N-dipropyl (meth)acrylamide, and N,N-diisopropyl (meth)acrylamide. As nitrogen-containing monomers for acrylic polymers, one nitrogen-containing monomer may be used, or two or more nitrogen-containing monomers may be used. In the present embodiment, N-vinyl-2-pyrrolidone is preferably used as a nitrogen-containing monomer for acrylic polymers.
[0079] The ratio of the monomer units derived from the nitrogen atom-containing monomer in the acrylic polymer is preferably 1% by weight or more, more preferably 3% by weight or more, and more preferably 5% by weight or more, from the viewpoint of achieving appropriate hardness, adhesion, and transparency in the photocurable adhesive matrix material formed by the acrylic polymer. In addition, the ratio of the monomer units derived from the nitrogen atom-containing monomer in the acrylic polymer is preferably 30% by weight or less, and more preferably 25% by weight or less, from the viewpoint of achieving sufficient transparency and preventing the polymer from becoming too hard and achieving good adhesion reliability in the photocurable adhesive matrix material formed by the acrylic polymer.
[0080] The acrylic polymer contained in the aforementioned photocurable adhesive matrix material may contain a monomer unit derived from a carboxyl group-containing monomer. A carboxyl group-containing monomer is a monomer having at least one carboxyl group in the monomer unit. When the acrylic polymer in the photocurable adhesive matrix material contains a carboxyl group-containing monomer unit, the photocurable adhesive matrix material may sometimes obtain good bonding reliability.
[0081] As the carboxyl-containing monomers used to form the monomer units of the acrylic acid polymer, that is, the carboxyl-containing monomers contained in the monomer components used to form the acrylic acid polymer, for example (meth) acrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid and isocrotonic acid can be listed. As the carboxyl-containing monomers used for acrylic acid polymers, one carboxyl-containing monomer can be used, or two or more carboxyl-containing monomers can be used. In the present embodiment, as the carboxyl-containing monomers used for acrylic acid polymers, acrylic acid is preferably used.
[0082] The ratio of the monomer units derived from the carboxyl group-containing monomer in the acrylic polymer is preferably 0.1% by weight or more, more preferably 0.5% by weight or more, in the light-curing adhesive matrix material formed by including the acrylic polymer, from the viewpoint of obtaining the contribution of the interaction between the polar group and the carboxyl group when the polar group exists on the adherend surface and ensuring good bonding reliability. In addition, the ratio of the monomer units derived from the carboxyl group in the acrylic polymer is preferably 20% by weight or less, more preferably 15% by weight or less, in the viewpoint of preventing the light-curing adhesive matrix material formed by including the acrylic polymer from becoming too hard and achieving good bonding reliability.
[0083] The acrylic polymer contained in the aforementioned photocurable adhesive matrix material may have a cross-linked structure derived from a multifunctional (meth)acrylate belonging to a copolymerizable crosslinking agent. As multifunctional (meth)acrylates, for example, 1,6-hexanediol di(meth)acrylate, butanediol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, allyl (meth)acrylate, and vinyl (meth)acrylate may be cited. As multifunctional (meth)acrylates for acrylic polymers, one multifunctional (meth)acrylate may be used, or two or more multifunctional (meth)acrylates may be used. In the present embodiment, as the polyfunctional (meth)acrylate used for the acrylic polymer, at least one selected from the group consisting of 1,6-hexanediol diacrylate, dipentaerythritol hexaacrylate, and trimethylolpropane triacrylate is preferably used.
[0084] The ratio of the monomer units derived from the multifunctional (meth)acrylate in the acrylic polymer is preferably 0.01% by weight or more, more preferably 0.03% by weight or more, more preferably 0.05% by weight or more, and more preferably 0.1% by weight or more. The ratio of the monomer units derived from the multifunctional (meth)acrylate in the acrylic polymer is preferably 1% by weight or less, more preferably 0.5% by weight or less. These structures related to the ratio of the multifunctional (meth)acrylate are suitable for achieving appropriate hardness and adhesion of the photocurable adhesive matrix material formed by the acrylic polymer.
[0085] When the photocurable adhesive matrix material contains the acrylic polymer as described above as a binder, the content of the acrylic polymer in the photocurable adhesive matrix material is, for example, 85 to 100% by weight.
[0086] The aforementioned photocurable adhesive matrix material contains a monomer for forming an acrylic polymer and a photopolymerization initiator. Examples of the aforementioned photopolymerization initiator include benzoin ether-based photopolymerization initiators, acetophenone-based photopolymerization initiators, α-ketol-based photopolymerization initiators, aromatic sulfonyl chloride-based photopolymerization initiators, photoactive oxime-based photopolymerization initiators, benzoin-based photopolymerization initiators, benzyl-based photopolymerization initiators, benzophenone-based photopolymerization initiators, ketal-based photopolymerization initiators, and thioxanthone-based photopolymerization initiators. Examples of the benzoin ether-based photopolymerization initiators include benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, and 2,2-dimethoxy-1,2-diphenylethane-1-one. As acetophenone-based photopolymerization initiators, for example, 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexyl phenyl ketone, 4-phenoxydichloroacetophenone and 4-(tert-butyl)dichloroacetophenone can be listed. As α-ketol-based photopolymerization initiators, for example, 2-methyl-2-hydroxypropiophenone and 1-[4-(2-hydroxyethyl)phenyl]-2-methylpropane-1-one can be listed. As aromatic sulfonyl chloride-based photopolymerization initiators, for example, 2-naphthalenesulfonyl chloride can be listed. As photoactive oxime-based photopolymerization initiators, for example, 1-phenyl-1,1-propanedione-2-(o-ethoxycarbonyl)oxime can be listed. As benzoin-based photopolymerization initiators, for example, benzoin can be listed. As benzil-based photopolymerization initiators, for example, benzil can be listed. Examples of benzophenone-based photopolymerization initiators include benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone, and polyvinylbenzophenone. Examples of ketal-based photopolymerization initiators include benzildimethylketal. Examples of thioxanthone-based photopolymerization initiators include thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, and dodecylthioxanthone. The photocurable adhesive matrix material may contain one or more of the photopolymerization initiators. The content of the photopolymerization initiator in the photocurable adhesive matrix material is, for example, 0.01 to 3% by weight.
[0087] The aforementioned photocurable adhesive matrix material may further contain additives such as crosslinking agent, crosslinking accelerator, silane coupling agent, tackifying resin, antioxidant, filler, coloring agent such as pigment and dye, antioxidant, chain transfer agent, plasticizer, softener, surfactant, rust inhibitor, antistatic agent, etc. as needed. Examples of the tackifying resin include rosin derivatives, polyterpene resins, petroleum resins, and oil-soluble phenols.
[0088] It should be noted that the aforementioned photocurable adhesive matrix material preferably does not contain or substantially does not contain an ultraviolet absorber. This configuration is preferred from the viewpoint that the deterioration of curability, the difference in physical properties between the front and back sides, the change in the peeling force of the peeling sheet, etc. can be controlled to a minimum when the adhesive sheet of the present invention is provided in the adhesive layer curing process described later. When the proportion of the ultraviolet absorber in the total amount (100% by mass) of the photocurable adhesive matrix material is less than 0.05% by weight (preferably less than 0.01% by mass), it can be said that the aforementioned photocurable adhesive matrix material substantially does not contain an ultraviolet absorber.
[0089] The method for forming the adhesive layer is not particularly limited, and examples thereof include: applying (coating) the photocurable adhesive matrix material on a support, and drying and curing the resulting adhesive composition layer; applying (coating) the photocurable adhesive matrix material on a support, and curing the resulting adhesive composition layer by irradiating active energy rays. If necessary, further heating and drying may be performed.
[0090] The aforementioned photocurable adhesive matrix material can be applied (coated) using a known coating method, for example, coating machines such as a gravure roll coater, a reverse roll coater, a kiss roll coater, a dip roll coater, a rod coater, a knife coater, a spray coater, a comma coater, and a direct coater.
[0091] The drying and curing temperature is preferably 40 to 200° C., more preferably 50 to 180° C., and further preferably 70 to 170° C. The drying and curing time can be appropriately selected from a suitable time, for example, 5 seconds to 20 minutes, preferably 5 seconds to 10 minutes, and more preferably 10 seconds to 5 minutes.
[0092] As the above-mentioned active energy rays, for example, ionizing radiation such as α rays, β rays, γ rays, neutron rays, electron rays, ultraviolet rays, etc. can be listed, and ultraviolet rays are particularly preferred. In addition, the irradiation energy, irradiation time, irradiation method, etc. of the active energy rays are not particularly limited, as long as they are appropriately set in a manner to achieve a desired viscosity and viscoelasticity according to the thickness of the adhesive layer 10, etc.
[0093] In order to block oxygen that inhibits curing by the active energy rays and / or ultraviolet irradiation described later, another support (including a release sheet) is preferably further laminated on the main surface of the adhesive layer formed above that does not face the support.
[0094] Then, if Figure 1 As shown in (b) of FIG. 1 , the adhesive layer 10 is irradiated with ultraviolet rays U to cure the adhesive layer 10 (adhesive layer curing step). Figure 1In (b), 10a is an adhesive layer obtained by curing the adhesive layer 10. Since the adhesive layer at this stage does not contain or substantially contains no ultraviolet absorber, it is possible to produce an adhesive layer 10a that is less likely to undergo changes in physical properties such as reduction in productivity caused by deterioration of curability due to the ultraviolet absorber, differences in physical properties between the front and back surfaces, and changes in the peeling force of the peeling sheet, and has high reliability.
[0095] The pressure-sensitive adhesive layer 10 may be irradiated with ultraviolet rays directly, but is preferably irradiated through a support in order to block oxygen that inhibits curing by ultraviolet irradiation. Figure 1 (b) is an embodiment of irradiating the adhesive layer 10 with ultraviolet rays through the support S2. When irradiating with ultraviolet rays through the support, another support S2 (including a release sheet) is attached to the main surface of the adhesive layer 10 on the opposite side of the main surface facing the support S1, and ultraviolet rays are irradiated through the support. The illumination and time of ultraviolet irradiation are appropriately set according to the composition of the photocurable adhesive matrix material, the thickness of the adhesive layer, etc. Ultraviolet irradiation can use a high-pressure mercury lamp, a low-pressure mercury lamp, a metal halide lamp, etc.
[0096] Then, if Figure 1 As shown in (c), after the support body S2 is peeled off and removed, the solution 12 of the ultraviolet absorber 11 is applied to one face of the adhesive layer 10a (solution coating process). The solution of the ultraviolet absorber is not particularly limited as long as it can be applied to the adhesive layer in a liquid state and penetrate. For example, when the ultraviolet absorber is in a liquid state, the ultraviolet absorber itself can be directly applied in the form of a solution. In addition, it can also be a solution obtained by dissolving the ultraviolet absorber in a solvent. Alternatively, it can be a solution formed by mixing the ultraviolet absorber with the pigment compound described later. Figure 1 (c) is an embodiment in which a solution 12 obtained by dissolving the ultraviolet absorber 11 in the solvent 13 is applied to one surface of the pressure-sensitive adhesive layer 10 a .
[0097] Regarding the surface of the adhesive layer 10a, the ultraviolet absorber 11 in the solution 12 permeates into the adhesive layer 10a along the thickness direction (solution permeation step). Figure 1 (d). When the solution 12 is a solution obtained by dissolving the ultraviolet absorber 11 in the solvent 13, the ultraviolet absorber 11 penetrates into the adhesive layer 10a while being dissolved in the solvent while the solvent 13 penetrates into the adhesive layer 10a. The ultraviolet absorber 11 is in a state of being "dissolved" in the adhesive layer 10a.
[0098] In addition, during the process of the ultraviolet absorber 11 penetrating into the adhesive layer 10a, a concentration gradient can be formed along the thickness direction. Therefore, the concentration of the ultraviolet absorber 11 on the side coated with the solution 12 can be higher than that on the opposite side. Figure 1 (d).
[0099] Thereafter, the adhesive layer 10a is dried to obtain Figure 1 The adhesive sheet 1 shown in (e) (drying process). When the solution 12 is a solution obtained by dissolving the ultraviolet absorber 11 in a solvent, the solvent 13 that has penetrated is evaporated by the drying process. By drying the adhesive layer 10a, the adhesive layer 10a is restored to a state close to that before coating. Therefore, the difference in physical properties between the front and back sides, the change in the peeling force of the peeling sheet, etc. can be controlled to a minimum. At the moment when the adhesive layer 10a is dried, the ultraviolet absorber 11 stops penetrating into the adhesive layer 10a, and the concentration gradient of the aforementioned ultraviolet absorber is fixed.
[0100] As the aforementioned ultraviolet absorber, there is no particular limitation, and examples thereof include triazine ultraviolet absorbers, benzotriazole ultraviolet absorbers, benzophenone ultraviolet absorbers, oxybenzophenone ultraviolet absorbers, salicylate ultraviolet absorbers, cyanoacrylate ultraviolet absorbers, etc., and one or more of them can be used alone or in combination. Among these, triazine ultraviolet absorbers, benzotriazole ultraviolet absorbers, and benzophenone ultraviolet absorbers are preferred. From the aspect of good solubility and high ultraviolet absorption capacity near a wavelength of 380nm, at least one ultraviolet absorber selected from the group consisting of triazine ultraviolet absorbers having two or less hydroxyl groups in one molecule, benzotriazole ultraviolet absorbers having one benzotriazole skeleton in one molecule, and benzophenone ultraviolet absorbers is preferred.
[0101] Specific examples of the triazine-based ultraviolet absorber having two or less hydroxyl groups in one molecule include 2,4-bis-[{4-(4-ethylhexyloxy)-4-hydroxy}-phenyl]-6-(4-methoxyphenyl)-1,3,5-triazine (Tinosorb S, manufactured by BASF), 2,4-bis[2-hydroxy-4-butoxyphenyl]-6-(2,4-dibutoxyphenyl)-1,3,5-triazine (TINUVIN460, manufactured by BASF), 2-(4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine-2-yl)-5-hydroxyphenyl and [(C 10 -C 16 (Mainly C 12 -C 13)alkoxy)methyl] ethylene oxide reaction product (TINUVIN400, manufactured by BASF), 2-[4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine-2-yl]-5-[3-(dodecyloxy)-2-hydroxypropoxy]phenol), reaction product of 2-(2,4-dihydroxyphenyl)-4,6-bis-(2,4-dimethylphenyl)-1,3,5-triazine and (2-ethylhexyl) glycidate (TINUVIN405, manufactured by BASF), 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-[(hexyl)oxy]-phenol (TINUVIN1577, manufactured by BASF), 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-[2-(2-ethylhexanoyloxy)ethoxy]-phenol (ADK STAB LA46, manufactured by ADEKA Corporation), 2-(2-hydroxy-4-[1-octyloxycarbonylethoxy]phenyl)-4,6-bis(4-phenylphenyl)-1,3,5-triazine (TINUVIN479, manufactured by BASF Corporation), and the like.
[0102] Examples of benzotriazole-based ultraviolet absorbers having one benzotriazole skeleton in one molecule include 2-(2H-benzotriazole-2-yl)-6-(1-methyl-1-phenylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol (TINUVIN 928, manufactured by BASF), 2-(2-hydroxy-5-tert-butylphenyl)-2H-benzotriazole (TINUVIN PS, manufactured by BASF), phenylpropionic acid, and 3-(2H-benzotriazole-2-yl)-5-(1,1-dimethylethyl)-4-hydroxy(C 7-9side chain and straight chain alkyl) ester compound (TINUVIN384-2, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol (TINUVIN900, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-6-(1-methyl-1-phenylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol (TINUVIN928, manufactured by BASF), methyl-3-(3-(2H-benzotriazol-2-yl)-5-tert-butyl-4-hydroxyphenyl) propionate / polyethylene glycol 300 reaction product (TINUVIN1130, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-p-cresol (TINUVIN P, BASF), 2-(2H-benzotriazol-2-yl)-4-6-bis(1-methyl-1-phenylethyl)phenol (TINUVIN234, BASF), 2-[5-chloro(2H)-benzotriazol-2-yl]-4-methyl-6-(tert-butyl)phenol (TINUVIN326, BASF), 2-(2H-benzotriazol-2-yl)-4,6-di-tert-amylphenol (TINUVIN328, BASF), 2-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol (TINUVIN TINUVIN329, manufactured by BASF), reaction product of methyl 3-(3-(2H-benzotriazol-2-yl)-5-tert-butyl-4-hydroxyphenyl)propionate and polyethylene glycol 300 (TINUVIN213, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-6-dodecyl-4-methylphenol (TINUVIN571, manufactured by BASF), 2-[2-hydroxy-3-(3,4,5,6-tetrahydrophthalimidomethyl)-5-methylphenyl]benzotriazole (Sumisorb250, manufactured by Sumitomo Chemical Industries, Ltd.), etc.
[0103] Examples of the benzophenone-based ultraviolet absorbers (benzophenone-based compounds) and oxybenzophenone-based ultraviolet absorbers (oxybenzophenone-based compounds) include 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid (anhydride and trihydrate), 2-hydroxy-4-octyloxybenzophenone, 4-dodecyloxy-2-hydroxybenzophenone, 4-benzyloxy-2-hydroxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone (Seesorb 106, manufactured by SHIPRO KASEI Co., Ltd.), and 2,2'-dihydroxy-4,4-dimethoxybenzophenone.
[0104] Examples of the salicylate ultraviolet absorber (salicylate compound) include phenyl 2-acryloxybenzoate, phenyl 2-acryloxy-3-methylbenzoate, phenyl 2-acryloxy-4-methylbenzoate, phenyl 2-acryloxy-5-methylbenzoate, phenyl 2-acryloxy-3-methoxybenzoate, phenyl 2-hydroxybenzoate, phenyl 2-hydroxy-3-methylbenzoate, phenyl 2-hydroxy-4-methylbenzoate, phenyl 2-hydroxy-5-methylbenzoate, phenyl 2-hydroxy-3-methoxybenzoate, phenyl 3,5-di-tert-butyl-4-hydroxybenzoate (TINUVIN 120, manufactured by BASF).
[0105] Examples of the cyanoacrylate ultraviolet absorber (cyanoacrylate compound) include 2-cyanoacrylate alkyl esters, 2-cyanoacrylate cycloalkyl esters, 2-cyanoacrylate alkoxyalkyl esters, 2-cyanoacrylate alkenyl esters, and 2-cyanoacrylate alkynyl esters.
[0106] The maximum absorption wavelength of the absorption spectrum of the ultraviolet absorber is preferably present in the wavelength region of 300 to 400 nm, more preferably in the wavelength region of 320 to 380 nm. The maximum absorption wavelength refers to the maximum absorption wavelength showing the maximum absorbance among a plurality of maximum absorption maxima in the spectral absorption spectrum in the wavelength region of 300 to 460 nm.
[0107] The solution of the ultraviolet absorber may further contain a pigment compound whose maximum absorption wavelength of the absorption spectrum exists in the wavelength region of 380 to 430 nm. Alternatively, a solution of the pigment compound different from the solution of the ultraviolet absorber may be applied to the adhesive layer 10a. The maximum absorption wavelength of the absorption spectrum of the pigment compound preferably exists in the wavelength region of 380 to 420 nm. The solution of the pigment compound may be a solution obtained by dissolving the pigment compound in a solvent.
[0108] By applying a solution containing a pigment compound whose maximum absorption wavelength of the absorption spectrum exists in the wavelength region of 380 to 430 nm in addition to an ultraviolet absorber to the adhesive layer 10a, light in the wavelength region (380 nm to 430 nm) on the longer wavelength side than the ultraviolet absorber can be fully absorbed, thereby more effectively suppressing the degradation of organic EL elements, etc.
[0109] Examples of the pigment compound include organic pigment compounds and inorganic pigment compounds. Among these, organic pigment compounds are preferred from the viewpoint of maintaining dispersibility and transparency in a resin component such as a matrix polymer.
[0110] Examples of the organic pigment compound include azomethine compounds, indole compounds, cinnamic acid compounds, pyrimidine compounds, porphyrin compounds, and cyanine compounds.
[0111] As the aforementioned organic pigment compound, commercially available products can be suitably used. Specifically, as the aforementioned indole compound, BONASORB UA3911 (trade name, maximum absorption wavelength of absorption spectrum: 398nm, half value width: 48nm, manufactured by ORIENT CHEMICAL INDUSTRIES) can be listed; as the cinnamic acid compound, SOM-5-0106 (trade name, maximum absorption wavelength of absorption spectrum: 416nm, half value width: 50nm, manufactured by ORIENT CHEMICAL INDUSTRIES) can be listed; as the porphyrin compound, FDB-001 (trade name, maximum absorption wavelength of absorption spectrum: 420nm, half value width: 14nm, manufactured by Yamada Chemical Industry Co., Ltd.) can be listed; as the cyanine compound, a merocyanine compound (trade name: FDB-009, maximum absorption wavelength of absorption spectrum: 394nm, half value width: 43nm, manufactured by Yamada Chemical Industry Co., Ltd.) can be listed.
[0112] The aforementioned solvent is not particularly limited as long as it is a solvent that can dissolve the aforementioned ultraviolet absorber and / or the aforementioned pigment compound and can cause the adhesive layer 10a to swell. From the perspective that aqueous solvents have poor wettability in the adhesive layer and additives are not easy to penetrate, non-aqueous solvents are preferred. The non-aqueous solvent is not particularly limited, and examples thereof include esters such as methyl acetate, ethyl acetate, isopropyl acetate, and butyl acetate; alcohols such as methanol, ethanol, n-propanol, isopropyl alcohol, n-butanol, isobutyl alcohol, sec-butanol, and tert-butanol; aromatic hydrocarbons such as toluene, xylene, and ethylbenzene; ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; alicyclic ketones such as cyclopentanone and cyclohexanone; aliphatic hydrocarbons such as hexane, heptane, and octane; alicyclic hydrocarbons such as cyclohexane; halogenated hydrocarbons such as chloroform, dichloromethane, and 1,2-dichloroethane; ethers such as diethyl ether, dimethoxyethane, tetrahydrofuran, and dioxane; amides such as N,N-dimethylformamide and N,N-dimethylacetamide; nitriles such as acetonitrile, propionitrile, and benzonitrile, preferably esters, alcohols, aromatic hydrocarbons, and ketones. The solvent may be used alone or in combination of two or more.
[0113] The concentration of the ultraviolet absorber in the solution can be appropriately set according to the desired ultraviolet absorption function to be imparted to the adhesive layer 10a, and can be selected from a range with an upper limit of 50% by weight or less (e.g., 1 to 50% by weight, 1 to 45% by weight, 1 to 40% by weight, 1 to 35% by weight, 1 to 30% by weight, 1 to 25% by weight, 1 to 20% by weight, 1 to 15% by weight, etc.) or a lower limit of 1% or more (e.g., 1 to 50% by weight, 2 to 50% by weight, 3 to 50% by weight, 4 to 50% by weight, 5 to 50% by weight). If the concentration of the ultraviolet absorber in the solution is within this range, the ultraviolet absorber can be dissolved, and the adhesive layer 10a can be fully swollen, thereby imparting a moderate ultraviolet absorption function to the adhesive layer 10a.
[0114] When the solution of the ultraviolet absorber contains the pigment compound or the solution of the pigment compound is applied separately, the concentration of the pigment compound can be appropriately set, and can be selected from, for example, 1 to 50% by weight, preferably 2 to 40% by weight, more preferably 3 to 30% by weight, and further preferably 5 to 20% by weight. If the concentration of the pigment compound in the solution is within this range, the pigment compound can be dissolved, and the adhesive layer 10a is given a moderate absorption function in a long wavelength region compared to ultraviolet rays.
[0115] The solution 12 may be applied (coated) to the adhesive layer 10a using a known coating method, such as a gravure roll coater, a reverse roll coater, a kiss roll coater, a dip roll coater, a rod coater, a knife coater, a spray coater, a comma coater, a direct coater, or the like.
[0116] The coating amount of the solution of the ultraviolet absorber and / or the pigment compound on the adhesive layer 10a can be appropriately set according to the desired ultraviolet absorption function to be imparted to the adhesive layer 10a, and can be, for example, 1 to 1000 μg / cm 2 , preferably 1 to 500 μg / cm 2 , more preferably 1 to 100 μg / cm 2 , more preferably 1 to 50 μg / cm 2 If the coating amount of the solution of the ultraviolet absorber and / or the aforementioned pigment compound is within this range, the ultraviolet absorber and / or the aforementioned pigment compound can be dissolved and sufficient ultraviolet and / or longer wavelength absorption function can be imparted to the adhesive layer 10a.
[0117] After the solution of the ultraviolet light absorber and / or the aforementioned pigment compound is applied to the adhesive layer 10a, it can be allowed to stand still as needed to allow the ultraviolet light absorber and / or the aforementioned pigment compound to penetrate. As the standing time, there is no particular limitation, and it can be appropriately selected from, for example, within 15 minutes, and can be selected from, for example, 1 second to 10 minutes, preferably within the range of 5 seconds to 5 minutes. As the standing temperature, it can be carried out at room temperature (about 10 to 30°C). When standing still under the above conditions, the ultraviolet light absorber and / or the aforementioned pigment compound can be fully penetrated into the adhesive layer 10a.
[0118] The heating and drying temperature in the drying step is preferably 40 to 200° C., more preferably 50 to 180° C., and further preferably 70 to 170° C. The drying time can be appropriately used for a suitable time, for example, 5 seconds to 20 minutes, preferably 5 seconds to 10 minutes, and more preferably 10 seconds to 5 minutes. By drying under the above conditions, the adhesive layer 10a can be restored to a state close to that before coating.
[0119] Figure 2 (a) is a cross-sectional view showing one embodiment of the adhesive sheet according to the second aspect of the present invention, Figure 2 (b) is a cross-sectional view showing another embodiment of the adhesive sheet according to the second aspect of the present invention.
[0120] If you refer to Figure 2 (a), then an adhesive sheet 2A of one embodiment of the present invention is composed of an optically transparent adhesive layer 21 and a support body S1, the support body is not adhered to a first main surface 21a of the adhesive layer 21, but is adhered to another second main surface 21b of the adhesive layer 21, and the support body S1 is formed by a peeling sheet.
[0121] If you refer to Figure 2 (b), then an adhesive sheet 2B of one embodiment of the present invention is composed of an optically transparent adhesive layer 21, a first support S2 and a second support S1, wherein the first support S2 is bonded to a first main surface 21a of the adhesive layer 21 and is formed by a release sheet, and the second support S1 is bonded to the other second main surface 21b of the adhesive layer 21 and is formed by a release sheet. The adhesive sheet 2B can be obtained by bonding the support S2 to the first main surface 21a of the adhesive sheet 2A.
[0122] exist Figure 2 In (a) and (b), the dashed line XX' is a line segment that divides the adhesive layer 21 into two equal parts along the thickness direction. When the thickness of the adhesive layer 21 is uneven, the dashed line XX' is a line segment that divides the thickness at each point into two equal parts.
[0123] exist Figure 2In the embodiment, the adhesive layer 21 is formed of a transparent photocurable adhesive matrix material and is a single layer having two opposite main surfaces (a first main surface and a second main surface). The adhesive layer 21 can be formed by the above-mentioned adhesive layer forming step and adhesive layer curing step, which is equivalent to Figure 1 Therefore, the adhesive layer 21 is preferably an adhesive layer that is cured by ultraviolet irradiation.
[0124] The adhesive layer being a "single layer" means that it is not a laminated structure. For example, an adhesive layer formed of a transparent photocurable adhesive matrix material is formed, and an adhesive layer formed of the same transparent photocurable adhesive matrix material is formed thereon to obtain a laminated structure, not a single layer. Similarly, an adhesive layer formed of a transparent photocurable adhesive matrix material in which an ultraviolet absorber is dissolved is formed, and an adhesive layer formed of a transparent photocurable adhesive matrix material in which an ultraviolet absorber is dissolved at a different concentration is formed thereon to obtain a laminated structure, not a single layer.
[0125] The thickness of the adhesive layer 21 is not particularly limited, but is generally 5 to 500 μm, preferably 5 to 400 μm, and more preferably 50 to 400 μm. If the thickness of the adhesive layer 21 is within this range, it is suitable for forming a concentration gradient of the ultraviolet absorber along the thickness direction of the adhesive layer 21 .
[0126] The total light transmittance of the adhesive layer 21 as a whole is not particularly limited, but is preferably 80% or more, preferably 90% or more, as measured in accordance with JIS K7361. The higher the total light transmittance of the adhesive layer 21, the more preferred. In addition, the haze value is preferably 1.5% or less, more preferably 1% or less.
[0127] The ultraviolet absorber 11 is dissolved in the adhesive layer 21. In the solution penetration step, the ultraviolet absorber is impregnated into the adhesive layer, so that the ultraviolet absorber can be dissolved in the adhesive layer. Here, "dissolved" means, for example, that the ultraviolet absorber is dissolved to a degree that can maintain the transparency of the adhesive layer, that is, to a degree that white turbidity caused by light scattering of the ultraviolet absorber does not occur. Specifically, it is preferred that the ultraviolet absorber is included in the adhesive layer in such a way that the haze value of the adhesive layer becomes 1.5% or less, preferably 1% or less. In the case where the pigment compound is included in the adhesive layer 21, the pigment compound is also dissolved in the adhesive layer.
[0128] The ultraviolet absorber 11 is formed by impregnating the ultraviolet absorber 11 into the adhesive layer 21 through the above-mentioned solution coating process, solution penetration process and drying process. Figure 2As shown, a concentration gradient of the ultraviolet absorber 11 can be generated along the thickness direction of the adhesive layer 21. Therefore, when the single-layer adhesive layer 21 is divided into two equal parts along the thickness direction, the concentration of the ultraviolet absorber in the area where one of the two main surfaces, that is, the first main surface 21a, belongs is different from the concentration of the ultraviolet absorber in the area where the other, that is, the second main surface 21b, belongs. The situation where the ultraviolet absorber does not exist in the area where the concentration of the ultraviolet absorber is low (the concentration of the ultraviolet absorber is 0) is also included in the scope of the present invention. The situation where the pigment compound is dissolved in the adhesive layer 21 can also produce a concentration difference and a concentration gradient between the front and back sides of the adhesive layer.
[0129] Regarding the concentration of the aforementioned ultraviolet absorber and / or the aforementioned pigment compound in the area to which the first main surface belongs, and the concentration of the aforementioned ultraviolet absorber and / or the aforementioned pigment compound in the area to which the second main surface belongs, when there is also a concentration gradient in each area, it refers to the average concentration of the ultraviolet absorber and / or the aforementioned pigment compound in each area.
[0130] Figure 2 (a) is an embodiment in which the second main surface 21b faces the support body S1, and the concentration of the ultraviolet absorber in the area belonging to the first main surface 21a is higher than the concentration of the ultraviolet absorber in the area belonging to the second main surface 21b, which can be obtained by coating a solution of the ultraviolet absorber on the first main surface 21a and penetrating the ultraviolet absorber from the first main surface 21a to the depth in the thickness direction in a state where the ultraviolet absorber is dissolved.
[0131] The second aspect of the adhesive sheet of the present invention can minimize changes in physical properties such as differences in physical properties such as adhesiveness and viscoelasticity between the front and back surfaces.
[0132] For example, the difference between the adhesive force (N / 10 mm) of the first main surface and the adhesive force (N / 10 mm) of the second main surface is, for example, 1.0 N / 10 mm or less, preferably 0.5 N / 10 mm or less, and more preferably 0.3 N / 10 mm or less.
[0133] The adhesive sheet of the second aspect of the present invention can be used to join transparent optical components to other optical components in image display devices such as liquid crystal image display devices and organic EL image display devices. As the aforementioned optical components, transparent cover components such as polarizing films, phase difference films, and cover glasses, and other various transparent optical components can be listed. In addition, a glass substrate formed with a transparent conductive layer such as a patterned ITO film is also included in the optical component of the present invention. In addition, the adhesive sheet of the second aspect of the present invention can also be suitably used as a surface protection film for preventing the aforementioned optical components from being damaged or dirt from adhering.
[0134] Figure 3 This is a cross-sectional view of an optical member laminate showing an example of the simplest embodiment using the adhesive sheet of the present invention. Figure 3 , the optical member stack 3 is composed of an optically transparent first optical member 31 and a second optical member 32, and the second optical member 32 is bonded to the first optical member 31 via an optically transparent adhesive layer 21. The optical member stack 3 is Figure 2 The first optical member 31 and the second optical member 32 are obtained by peeling off the support bodies S1 and S2 from the adhesive sheet 2B shown in (b) and bonding them to the first optical member 31 and the second optical member 32. The transparent first optical member 31 and the second optical member 32 can be composed of a polarizing film, a phase difference film, other optical films used in an optical display device, or a transparent cover member such as a cover glass on the identification side of an optical display device. The first optical member 31 is bonded to the first main surface 21a of the adhesive layer 21, and the second optical member 32 is bonded to the second main surface 21b of the adhesive layer 21.
[0135] Figure 4 This is a cross-sectional view showing an embodiment of applying an adhesive layer 21 to a structure in which a transparent conductive layer 42 such as a patterned ITO film is formed on the adhesive layer side surface of an optical member 41 in order to form a touch panel sensor. Examples of the optical member 41 in this case include a glass substrate of a display panel in a liquid crystal display device or an organic EL display device.
[0136] like Figure 4 As shown in the figure, the main surface 21b of the adhesive layer 21 is bonded to both the adhesive layer side surface of the second optical member 41 and the transparent conductive layer 42 in a manner that fills the height difference between the optical member 41 and the transparent conductive layer 42. Figure 2 After the support S2 of the adhesive sheet 2B shown in (b) is peeled off, the optical member 41 having the transparent conductive layer 42 formed thereon is bonded to the main surface 21 b and the support S1 is peeled off as necessary to obtain the optical member 41 .
[0137] Example
[0138] Hereinafter, the present invention will be described in more detail based on Examples, but the present invention is not limited to these Examples.
[0139] (Preparation of Adhesive Sheet A)
[0140] To a monomer mixture consisting of 66 parts by weight of 2-ethylhexyl acrylate (2EHA), 19 parts by weight of 2-hydroxyethyl acrylate (HEA) and 15 parts by weight of N-vinyl-2-pyrrolidone (NVP) were added 0.035 parts by weight of a photopolymerization initiator (trade name "Irgacure 184", manufactured by BASF) and 0.035 parts by weight of a photopolymerization initiator (trade name "Irgacure 651", manufactured by BASF), and then irradiated with ultraviolet rays until the viscosity (measurement conditions: BH viscometer No. 5 rotor, 10 rpm, measurement temperature: 30°C) reached about 20 Pa·s, thereby obtaining a prepolymer composition in which part of the above-mentioned monomer components was polymerized.
[0141] Next, 0.15 parts by weight of hexanediol diacrylate (HDDA) was added to the prepolymer composition and mixed to obtain an acrylic adhesive composition. The acrylic adhesive composition was applied to the peeling-treated surface of a release film (trade name "MRF#38", manufactured by Mitsubishi Resins) in such a manner that the thickness of the adhesive layer after formation was 100 μm to form an adhesive composition layer. Next, a release film (trade name "MRN#38", manufactured by Mitsubishi Resins) was attached to the surface of the adhesive composition layer. Thereafter, the adhesive composition layer was subjected to an irradiation of 5 mW / cm 2 , Light intensity: 1500mJ / cm 2 The adhesive composition layer is photocured by ultraviolet irradiation under conditions of , to form an adhesive sheet A.
[0142] (Preparation of Adhesive Sheet B)
[0143] An adhesive sheet B was formed in the same manner as the adhesive sheet A except that the added amount of hexanediol diacrylate (HDDA) was changed to 0.1 parts by weight.
[0144] (Preparation of Adhesive Sheet C)
[0145] Adhesive sheet C was formed by the same operation as Adhesive sheet A except that 96 parts by weight of butyl acrylate (BA) and 4 parts by weight of acrylic acid (AA) were used as the monomer mixture, and 0.1 parts by weight of 2-hydroxyethyl acrylate (HEA) was used instead of hexanediol diacrylate (HDDA). The thickness of the adhesive layer after formation was set to 23 μm.
[0146] (Preparation of Adhesive Sheet D)
[0147] As the monomer mixture, 57 parts by weight of butyl acrylate (BA), 23 parts by weight of 4-hydroxybutyl acrylate (4HBA), 8 parts by weight of 2-hydroxyethyl acrylate (HEA) and 12 parts by weight of cyclohexyl acrylate (CHA) were used, and 0.02 parts by weight of dipentaerythritol hexaacrylate (DPHA) was used instead of hexanediol diacrylate (HDDA). The thickness of the adhesive layer after formation was set to 150 μm. Except for this, the same operation as adhesive sheet A was performed to form adhesive sheet D.
[0148] (Preparation of Adhesive Sheet E)
[0149] Adhesive sheet E was formed in the same manner as Adhesive sheet A except that 29 parts by weight of 2-ethylhexyl acrylate (2EHA), 21 parts by weight of 4-hydroxybutyl acrylate (4HBA), 29 parts by weight of isostearyl acrylate (ISTA), and 21 parts by weight of isobornyl acrylate (IBXA) were used as the monomer mixture.
[0150] (Preparation of Adhesive Sheet F)
[0151] As the monomer mixture, 41 parts by weight of 2-ethylhexyl acrylate (2EHA), 1 part by weight of 4-hydroxybutyl acrylate (4HBA), 17 parts by weight of N-vinyl-2-pyrrolidone (NVP) and 41 parts by weight of isostearyl acrylate (ISTA) were used, and 0.02 parts by weight of trimethylolpropane triacrylate (TMPTA) was used instead of hexanediol diacrylate (HDDA). Except for this, the same operation as that of adhesive sheet A was carried out to form adhesive sheet F.
[0152] (Example 1)
[0153] The release film on one main surface (referred to as the "first surface") of the adhesive sheet A was peeled off, and a 10 wt% ethyl acetate solution of a UV absorber (TinosorbS, manufactured by BASF) was applied to the exposed first surface using a wire wound rod type, No. 7 bar coater manufactured by RD Specialties. After coating, the adhesive sheet A was heated and dried in an oven at 110° C. for 2 minutes to volatilize and remove the solvent, thereby obtaining an adhesive sheet A including an adhesive layer in which the UV absorber was dissolved.
[0154] (Example 2)
[0155] The same procedures as in Example 1 were performed except that a solution obtained by dissolving 10 wt % of Tinosorb S (manufactured by BASF) as a UV absorber and FDB-009 (manufactured by Yamada Chemical Industry Co., Ltd., maximum absorption wavelength of the absorption spectrum: 394 nm) as a pigment compound in ethyl acetate was applied to obtain an adhesive sheet A including an adhesive layer in which the UV absorber and the pigment compound were dissolved.
[0156] (Comparative Example 1)
[0157] The release film on the first surface of the adhesive sheet A was peeled off, and the adhesive sheet A on which the ultraviolet absorber solution was not applied was used as Comparative Example 1.
[0158] (Example 3)
[0159] Using the adhesive sheet B, except that a 12 wt % ethyl acetate solution of an ultraviolet absorber (Tinuvin 928, manufactured by BASF) was applied, the same operation as in Example 1 was performed to obtain an adhesive sheet B including an adhesive layer in which the ultraviolet absorber was dissolved.
[0160] (Example 4)
[0161] The same procedure as in Example 1 was carried out except that a 12 wt % methyl ethyl ketone solution of an ultraviolet absorber (Tinuvin 928, manufactured by BASF) was applied to the adhesive sheet B to obtain an adhesive layer B in which the ultraviolet absorber was dissolved.
[0162] (Example 5)
[0163] The same procedures as in Example 1 were carried out except that a 15 wt % ethyl acetate solution of a UV absorber (Seesorb 106, manufactured by SHIPRO KASEI) was applied to the adhesive sheet B to obtain an adhesive sheet B including an adhesive layer in which the UV absorber was dissolved.
[0164] (Comparative Example 2)
[0165] The release film on the first surface of the adhesive sheet B was peeled off, and the adhesive sheet B on which the ultraviolet absorber solution was not applied was used as Comparative Example 2.
[0166] (Example 6)
[0167] A pressure-sensitive adhesive sheet C including a pressure-sensitive adhesive layer in which a UV absorber (Tinosorb S, manufactured by BASF) was dissolved was obtained in the same manner as in Example 1 except that the pressure-sensitive adhesive sheet C was used.
[0168] (Example 7)
[0169] Using the adhesive sheet C, except that an ethyl acetate solution having a concentration of 12 wt % of an ultraviolet absorber (Tinuvin 928, manufactured by BASF) was applied, the same procedures as in Example 1 were carried out to obtain an adhesive sheet C including an adhesive layer in which an ultraviolet absorber was dissolved.
[0170] (Example 8)
[0171] Using the adhesive sheet C, except that a 12 wt % methyl ethyl ketone solution of an ultraviolet absorber (Tinuvin 928, manufactured by BASF) was applied, the same procedures as in Example 1 were carried out to obtain an adhesive sheet C including an adhesive layer in which an ultraviolet absorber was dissolved.
[0172] (Example 9)
[0173] The same procedures as in Example 1 were carried out except that a 15 wt % ethyl acetate solution of a UV absorber (Seesorb 106, manufactured by SHIPRO KASEI) was applied to the adhesive sheet C to obtain an adhesive sheet C including an adhesive layer in which the UV absorber was dissolved.
[0174] (Comparative Example 3)
[0175] The release film on the first surface of the adhesive sheet C was peeled off, and the adhesive sheet C on which the ultraviolet absorber solution was not applied was used as Comparative Example 3.
[0176] (Comparative Example 4)
[0177] Using the adhesive sheet C, except that ethyl acetate containing no ultraviolet absorber was applied, the same operation as in Example 1 was carried out to obtain an adhesive sheet C containing no ultraviolet absorber.
[0178] (Example 10)
[0179] A PSA sheet D including a PSA layer in which a UV absorber (Tinosorb S, manufactured by BASF) was dissolved was obtained in the same manner as in Example 1 except that the PSA sheet D was used.
[0180] (Comparative Example 5)
[0181] The release film on the first surface of the pressure-sensitive adhesive sheet D was peeled off, and the pressure-sensitive adhesive sheet D on which the ultraviolet absorber solution was not applied was used as Comparative Example 5.
[0182] (Example 11)
[0183] A PSA sheet E including a PSA layer in which a UV absorber (Tinosorb S, manufactured by BASF) was dissolved was obtained in the same manner as in Example 1 except that the PSA sheet E was used.
[0184] (Comparative Example 6)
[0185] The release film on the first surface of the adhesive sheet F was peeled off, and an adhesive sheet E on which the ultraviolet absorber solution was not applied was used as Comparative Example 6.
[0186] (Example 12)
[0187] A pressure-sensitive adhesive sheet F including a pressure-sensitive adhesive layer in which a UV absorber (Tinosorb S, manufactured by BASF) was dissolved was obtained in the same manner as in Example 1 except that the pressure-sensitive adhesive sheet F was used.
[0188] (Comparative Example 7)
[0189] The release film on the first surface of the pressure-sensitive adhesive sheet F was peeled off, and the pressure-sensitive adhesive sheet F on which the ultraviolet absorber solution was not applied was used as Comparative Example 7.
[0190] (Comparative Example 8)
[0191] Using the adhesive sheet F, except that ethyl acetate containing no ultraviolet absorber was applied, the same operation as in Example 1 was carried out to obtain an adhesive sheet F containing no ultraviolet absorber.
[0192] (Comparative Example 9)
[0193] A pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer in which the pressure-sensitive adhesive layer was uniformly dissolved was obtained in the same manner as in pressure-sensitive adhesive sheet D, except that 70 parts by weight of butyl acrylate (BA), 14 parts by weight of 4-hydroxybutyl acrylate (4HBA), and 16 parts by weight of N-vinyl-2-pyrrolidone (NVP) were used as the monomer mixture, and 0.0009 parts by weight of a UV absorber (Tinosorb S, manufactured by BASF) was further added to the acrylic pressure-sensitive adhesive composition.
[0194] The following evaluations were performed using the adhesive sheets obtained in Examples 1 to 12 and Comparative Examples 1 to 8.
[0195] <Transmittance Evaluation>
[0196] The release films of the adhesive sheets obtained in Examples and Comparative Examples were peeled off, and the transmittance at each light wavelength (wavelength range: 300 to 800 nm) was evaluated using a spectrophotometer (U4100, manufactured by Hitachi High-Technologies Corporation).
[0197] <Adhesion Evaluation>
[0198] The release film of the adhesive sheet obtained in the examples and comparative examples was peeled off, and the surface coated with the ultraviolet absorber solution was made the first surface, and the opposite main surface was made the second surface.
[0199] The obtained adhesive sheet was cut into 100 mm wide and 100 mm long, and the first or second side was bonded to the alkali glass, and a PET film (thickness: 25 μm) was bonded to the reverse side, and bonded using a manual roller, and heated and pressurized in an autoclave (5 atm, 50°C) for 15 minutes. The adhesive force (N / 10mm) of the sample obtained by such operation was measured using AUTOGRAPH (tensile speed: 60 mm / min. Peeling angle: 180°). In the measurement, 3 samples were made for each condition, and their numerical average was taken. The adhesive force (N / 10mm) of the first and second sides relative to the alkali glass and their difference are shown in Table 1.
[0200] [Table 1]
[0201]
[0202] According to Table 1, it is clear that by applying a solution of an ultraviolet absorber on the adhesive layer of the adhesive sheet cured by ultraviolet rays, it is possible to give the adhesive layer an excellent ultraviolet absorption function. It is also clear that by using the type of ultraviolet absorber in combination with the pigment compound, the wavelength absorption can be selectively controlled even in the ultraviolet region. In addition, it is known that by making the difference in adhesive force between the first side and the second side of the adhesive layer 1.0N / mm, and applying a solution of an ultraviolet absorber on the adhesive layer of the cured adhesive sheet, the difference in physical properties such as the adhesive force between the front and back sides of the adhesive layer can be controlled to a minimum.
[0203] <Evaluation of Distribution of Ultraviolet Absorber in the Thickness Direction of Adhesive>
[0204] TOF-SIMS analysis (Ar gas cluster ion etching method) was performed to examine the distribution state of the ultraviolet absorber (Tinosorb S) in the thickness direction of Example 10 and Comparative Example 9. Samples stored for one month after production were used.
[0205] The release films of the adhesive sheets obtained in Example 10 and Comparative Example 9 were peeled off, and TOF-SIMS analysis was performed from the first surface side under the following measurement conditions. The results are shown in FIG. Figure 5 . Figure 5 (a) is the result of Example 10, Figure 5 (b) is the result of Comparative Example 9. Figure 5 In the figure, the scale of the left vertical axis represents the intensity of butyl acrylate (BA, C3+H3+O2) and N-vinyl pyrrolidone (NVP, C4+H6+N+O), and the scale of the right vertical axis represents the intensity of ultraviolet absorber (Tinosorb S, C 30 +H 32 +N3+O5) intensity.
[0206] Analysis device: TOF-SIMS (ULVAC-PHI, TRIFT V)
[0207] Etching ions: Ar gas cluster ions
[0208] Irradiated primary ion: Bi3 2+
[0209] Accelerating voltage: 30 kV
[0210] Determination of polarity: negative ions
[0211] according to Figure 5 (a) shows that the adhesive layer of the adhesive sheet of Example 10 has a concentration gradient of the ultraviolet absorber (Tinosorb S) from the first surface to the second surface. Figure 5 (b) shows that the ultraviolet absorber (Tinosorb S) is distributed at a constant concentration from the first surface to the second surface of the adhesive layer of the adhesive sheet of Comparative Example 9.
[0212] Modifications of the present invention are described below.
[0213] [Supplementary Note 1] A method for producing an adhesive sheet, characterized in that it comprises the following steps:
[0214] forming an adhesive layer composed of a transparent photocurable adhesive matrix material on a support,
[0215] irradiating the adhesive layer with ultraviolet rays to cure the adhesive layer,
[0216] Prepare a solution of UV absorber,
[0217] The solution is applied to one surface of the cured adhesive layer so that the ultraviolet absorber contained in the solution penetrates from the one surface of the adhesive layer in the thickness direction.
[0218] The adhesive layer is allowed to dry.
[0219] [Supplementary Note 2] The method for producing a pressure-sensitive adhesive sheet according to Supplementary Note 1, wherein the solution of the ultraviolet absorber is a solution obtained by dissolving the ultraviolet absorber in a solvent,
[0220] The manufacturing method comprises the following steps:
[0221] The solvent of the solution is evaporated by drying the adhesive layer.
[0222] [Appendix 3] The method for producing a pressure-sensitive adhesive sheet according to Appendix 1 or 2, wherein the solution of the ultraviolet absorber further contains a pigment compound having a maximum absorption wavelength in an absorption spectrum in a wavelength range of 380 to 430 nm.
[0223] [Supplement 4] The method for producing an adhesive sheet according to Supplement 1 or 2, further comprising the following step:
[0224] A solution of a dye compound having a maximum absorption wavelength in an absorption spectrum in a wavelength region of 380 to 430 nm is prepared, and the solution is applied to one surface of the cured pressure-sensitive adhesive layer.
[0225] [Appendix 5] The method for producing a pressure-sensitive adhesive sheet according to Appendix 4, wherein the solution of the pigment compound is a solution obtained by dissolving the pigment compound in a solvent.
[0226] [Appendix 6] The method for producing an adhesive sheet according to any one of Appendices 1 to 5, further comprising the following step:
[0227] A release sheet is attached to the surface of the pressure-sensitive adhesive layer on the opposite side to the support.
[0228] [Supplementary Note 7] The method for producing a pressure-sensitive adhesive sheet according to any one of Supplementary Notes 1 to 6, wherein the maximum absorption wavelength of the absorption spectrum of the ultraviolet absorber exists in a wavelength region of 300 to 400 nm.
[0229] [Supplementary Note 8] An adhesive sheet comprising a support and a transparent adhesive layer on the support,
[0230] The adhesive layer is formed of a transparent photocurable adhesive matrix material and is a single layer having two opposing main surfaces.
[0231] A UV absorber is dissolved in the adhesive layer.
[0232] When the single adhesive layer is divided into two equal parts along the thickness direction,
[0233] The concentration of the ultraviolet absorber in a region to which one of the two main surfaces, ie, the first main surface, belongs is different from the concentration of the ultraviolet absorber in a region to which the other main surface, ie, the second main surface, belongs.
[0234] [Appendix 9] The adhesive sheet according to Appendix 8, wherein the adhesive layer further contains a pigment compound having a maximum absorption wavelength in an absorption spectrum in a wavelength range of 380 to 430 nm dissolved therein.
[0235] [Supplementary Note 10] The adhesive sheet according to Supplementary Note 8 or 9, wherein a difference between the adhesive force (N / 10 mm) of the first main surface and the adhesive force (N / 10 mm) of the second main surface is 1.0 N / 10 mm or less.
[0236] [Appendix 11] The adhesive sheet according to any one of Appendices 8 to 10, wherein the adhesive layer is an adhesive layer that is cured by ultraviolet irradiation.
[0237] [Appendix 12] The adhesive sheet according to any one of Appendices 8 to 11, wherein the second main surface faces the support, and the concentration of the ultraviolet absorber in the region to which the first main surface belongs is higher than the concentration of the ultraviolet absorber in the region to which the second main surface belongs.
[0238] [Appendix 13] The adhesive sheet according to any one of Appendices 8 to 12, wherein the single-layer photocurable adhesive layer has a concentration gradient of the ultraviolet absorber along a thickness direction.
[0239] [Supplementary Note 14] The adhesive sheet according to any one of Supplementary Notes 8 to 13, wherein the support is formed of a release sheet.
[0240] [Supplementary Note 15] The adhesive sheet according to Supplementary Note 14, wherein the support body formed of a release sheet is disposed on both surfaces of the adhesive layer.
[0241] [Supplementary Note 16] The adhesive sheet according to any one of Supplementary Notes 8 to 15, wherein the maximum absorption wavelength of the absorption spectrum of the ultraviolet absorber exists in a wavelength region of 300 to 400 nm.
[0242] [Appendix 17] The adhesive sheet according to any one of Appendices 8 to 16, wherein the adhesive layer has a thickness of 5 to 500 μm.
[0243] Industrial Applicability
[0244] The present invention is useful for a method for producing a pressure-sensitive adhesive sheet having a transparent pressure-sensitive adhesive layer that can be used to bond a transparent optical member to another optical member, and a pressure-sensitive adhesive sheet obtainable by the production method.
[0245] Description of Reference Numerals
[0246] 10 adhesive layers (before UV based curing)
[0247] 10a Adhesive layer (after UV-based curing)
[0248] S1, S2 support (peel sheet)
[0249] U: Ultraviolet
[0250] 11. UV absorber
[0251] 12. Solution of UV absorber
[0252] 13 Solvents
[0253] 21 Adhesive layer (after UV-based curing)
[0254] 21a Main surface (first surface)
[0255] 21b Main surface (second surface)
[0256] 31, 32, 41 optical components
[0257] 42Transparent conductive layer
Claims
1. An adhesive sheet, characterized in that: The invention comprises a support and a transparent adhesive layer on the support, The adhesive layer is formed of a transparent photocurable adhesive matrix material and is a single layer having two opposing main surfaces. A UV absorber is dissolved in the adhesive layer. When the single adhesive layer is divided into two equal parts along the thickness direction, The concentration of the ultraviolet absorber in a region to which one of the two main surfaces, namely the first main surface, belongs is different from the concentration of the ultraviolet absorber in a region to which the other main surface, namely the second main surface, belongs. The difference between the adhesive force of the first main surface and the adhesive force of the second main surface is 1.0 N / 10 mm or less.
2. The adhesive sheet according to claim 1, wherein The adhesive layer further contains a pigment compound having a maximum absorption wavelength in an absorption spectrum in the wavelength region of 380 to 430 nm dissolved therein.
3. The adhesive sheet according to claim 1 or 2, wherein The adhesive layer is an adhesive layer that is cured by ultraviolet irradiation.
4. The adhesive sheet according to claim 1 or 2, characterized in that: The second main surface faces the support, and the concentration of the ultraviolet absorber in a region to which the first main surface belongs is higher than the concentration of the ultraviolet absorber in a region to which the second main surface belongs.
5. The adhesive sheet according to claim 1 or 2, characterized in that: The single-layer photocurable adhesive layer has a concentration gradient of the ultraviolet absorber along a thickness direction.
6. The adhesive sheet according to claim 1 or 2, characterized in that: The support is formed of a release sheet.
7. The adhesive sheet according to claim 6, characterized in that The support body formed of a release sheet is arranged on both surfaces of the pressure-sensitive adhesive layer.
8. The adhesive sheet according to claim 1 or 2, characterized in that: The maximum absorption wavelength of the absorption spectrum of the ultraviolet absorber exists in the wavelength region of 300 to 400 nm.
9. The adhesive sheet according to claim 1 or 2, wherein The thickness of the adhesive layer is 5 to 500 μm.
Citation Information
Patent Citations
Transparent double-sided adhesive sheet for image display device, and image display device
JP2012211305A
Photosetting adhesive sheet, adhesive sheet and image display device
JP2016222914A
